Binder for power storage device, binder solution for power storage device, power storage device electrode slurry, power storage device electrode, and power storage device
By using binders containing vinyl alcohol-based polymers and specific compounds, the problems of foaming and high resistance in the manufacturing of electrodes of power storage equipment are solved, and high peel strength, low resistance and anti-foaming performance are achieved, and the energy density and high-speed charging capacity of the battery are improved.
Patent Information
- Application Number
- CN202380053226.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-07-10
- Publication Date
- 2025-03-04
AI Technical Summary
During the manufacturing process of the electrodes of existing power storage equipment, fine bubbles are prone to appear, resulting in insufficient dispersion of particles and pores and stripes-like defects in the mixed layer. The large amount of bonding agent leads to high resistance, making it difficult to maintain capacity during high-speed charging.
The adhesive for power storage equipment containing a vinyl alcohol-based polymer and a specific compound is used to adjust the composition and structure of the polymer, and the peel strength and resistance characteristics of the adhesive are improved, and foaming is suppressed.
The electrode's high peel strength, low resistance and anti-foaming performance are achieved, and the battery's energy density and high-speed charging ability are improved.
Smart Images

Figure CN119563246A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a binder for an electrical storage device, a binder solution for an electrical storage device, an electrical storage device electrode slurry, an electrical storage device electrode, and an electrical storage device. Background Art
[0002] In recent years, portable terminals such as mobile phones, notebook personal computers, and tablet information terminals have become significantly popular. Portable terminals are required to be more comfortable and portable. With the rapid development of miniaturization, thinness, lightness, and high performance, the batteries used in portable terminals are also required to be miniaturized, thinned, lightened, and high-performance. As a power storage device used in the power supply of such portable terminals, lithium-ion secondary batteries are commonly used. Power storage devices such as lithium-ion secondary batteries have the following structure: a positive electrode and a negative electrode are provided with a separator, and are contained in a container together with an electrolyte obtained by dissolving a lithium salt such as LiPF6, LiBF4, LiTFSI (lithium bistrifluoromethanesulfonyl imide), and LiFSI (lithium bisfluorosulfonyl imide) in an organic liquid such as ethylene carbonate.
[0003] The negative electrode and positive electrode constituting the power storage device are usually prepared according to the following steps. First, a binder and a thickener are dissolved or dispersed in water or a solvent, and an active material, a conductive aid (conductive agent), etc. are mixed therein to obtain an electrode slurry. The obtained electrode slurry is applied to a collector and dried. Thus, an electrode having a mixed layer containing an active material, etc. formed on the collector is obtained.
[0004] From the viewpoint of reducing the burden on the environment and the simplicity of the manufacturing device, especially in the manufacture of the negative electrode, the transfer to the electrode slurry using the aqueous medium is carried out quickly. As such aqueous medium binders, binders of vinyl alcohol polymers, acrylic acid and other acrylic acid polymers, amide / imide polymers, etc. are known (e.g., Patent Documents 1 and 2).
[0005] On the other hand, in the manufacture of the positive electrode, an electrode slurry using a solvent is generally used. As the solvent, organic solvents such as N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylmethanesulfonamide, hexamethylphosphorus triamide can be cited. As such an organic solvent binder, vinylidene fluoride polymers, tetrafluoroethylene polymers, fluororubbers, etc. are known (e.g., Patent Documents 3 and 4).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 11-250915
[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-59527
[0010] Patent Document 3: Japanese Patent Application Publication No. 2017-107827
[0011] Patent Document 4: Japanese Patent Application Publication No. 2013-37955 Summary of the invention
[0012] Problems to be solved by the invention
[0013] In order to further miniaturize, thinn, and lighten the storage device, the energy density of both the negative electrode and the positive electrode is required to be improved. Therefore, there is an increasing demand for electrodes with reduced binder content and increased active material content, and electrodes with high peel strength are sought even for compositions with low binder content.
[0014] In addition, in order to shorten the charging time, a battery is sought that can suppress the capacity reduction compared to low-speed charging even when charging at a high speed. It is believed that the capacity reduction during high-speed charging is mainly caused by energy loss associated with internal resistance, and electrodes with low resistance are sought.
[0015] In addition, in the process of making electrode slurry, sometimes fine bubbles are wrapped into the slurry due to the mechanical stirring of the mixer, active materials, conductive additives and other powders. In the state containing the bubbles, there are the following problems: it is impossible to effectively transfer mechanical energy by mixing, so the particles are not fully dispersed, or if the electrode slurry is further applied in the state containing bubbles, the resulting mixed layer will produce fine holes, stripe defects, etc. Therefore, an electrode material that can suppress foaming when making electrode slurry is sought.
[0016] In view of the above problems, the purpose of the present application is to provide a binder for a storage device that has excellent peel strength when used for an electrode, is suitable for obtaining an electrode with low resistance, and can suppress foaming. In addition, its purpose is to provide a binder solution for a storage device, a storage device electrode slurry, a storage device electrode, and a storage device.
[0017] Means used to solve problems
[0018] As a result of intensive studies, the present inventors have found that the above-mentioned problems can be solved by a binder for an electrical storage device having a predetermined composition.
[0019] That is, the present invention includes the following technical solutions.
[0020] [1] A binder for an electrical storage device comprising a vinyl alcohol polymer and a compound represented by the following formula (1).
[0021] [Chemistry 1]
[0022]
[0023] In formula (1), R 1 and R 2 Each independently represents an alkyl group having 1 to 4 carbon atoms. m and n each independently represent an integer of 0 to 25.
[0024] [2] The binder for a storage device according to [1], wherein the vinyl alcohol polymer contains a structural unit derived from an ethylenically unsaturated dicarboxylic acid monomer, and the content of the structural unit is 0.01 mol% to 10 mol% relative to all structural units constituting the vinyl alcohol polymer, and the degree of saponification of the vinyl alcohol polymer is 60.0 mol% to 99.9 mol%.
[0025] [3] The binder for an electrical storage device according to [2], wherein the ethylenically unsaturated dicarboxylic acid monomer comprises at least one selected from the group consisting of maleic acid, monoalkyl maleate, dialkyl maleate, maleic anhydride, monoalkyl fumarate, and dialkyl fumarate.
[0026] [4] The binder for a storage battery device according to any one of [1] to [3], wherein R 1 is methyl, R 2 isobutyl, and m and n are less than 8 respectively.
[0027] [5] An electrical storage device binder solution comprising the electrical storage device binder according to any one of [1] to [4] and a solvent.
[0028] [6] An electrical storage device electrode slurry comprising the electrical storage device binder solution of [5] and an active material.
[0029] [7] The electrical storage device electrode slurry according to [6], wherein the content of the electrical storage device binder is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material.
[0030] [8] An electric storage device electrode comprising a solidified body of the electric storage device electrode slurry according to [6] or [7] and a current collector.
[0031] [9] An electric storage device comprising the electric storage device electrode of [8].
[0032] Effects of the Invention
[0033] In the present invention, the electrical storage device binder, the electrical storage device binder solution, the electrical storage device electrode slurry, the electrical storage device electrode, and the electrical storage device are excellent in peel strength, electrical resistance characteristics, and anti-foaming. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that it does not mean that the present invention is limited to the following embodiments. It should be noted that in this specification, the upper limit and lower limit of the numerical range (the content of each component, the value calculated by each component, and each physical property, etc.) can be appropriately combined. In addition, the numerical range represented by "~" means including the upper limit and lower limit. That is, "A~B" means "above A and below B".
[0035] <Binder for power storage devices>
[0036] In the present invention, the binder for an electrical storage device (hereinafter also referred to as "binder") is a binder for an electrical storage device comprising a vinyl alcohol polymer and a compound represented by the following formula (1). In the present invention, a preferred embodiment of the binder for an electrical storage device is a binder for an electrical storage device electrode.
[0037] [Chemistry 2]
[0038]
[0039] In formula (1), R 1 and R 2 Each independently represents an alkyl group having 1 to 4 carbon atoms. m and n each independently represent an integer of 0 to 25.
[0040] [Vinyl alcohol polymer]
[0041] A vinyl alcohol polymer (also referred to as "PVA" in this specification) is a polymer having a vinyl alcohol unit as a structural unit. PVA is obtained by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer as its raw material monomer, and the saponified PVA may contain a vinyl ester unit in addition to the vinyl alcohol unit.
[0042] Regarding PVA, a copolymer obtained by copolymerizing a vinyl ester monomer as its raw material monomer with other monomers is saponified to produce a PVA containing structural units other than vinyl alcohol units and vinyl ester units. In the present application, such PVA is referred to as a "modified vinyl alcohol polymer (modified PVA)". In addition, among the raw material monomers of the modified PVA, monomers other than vinyl ester monomers are sometimes referred to as "modified species". In addition, the polymer before saponification of the (modified) PVA is sometimes referred to as a (modified) vinyl ester polymer. It should be noted that a "modified vinyl ester polymer" refers to a vinyl ester polymer containing structural units other than vinyl ester units.
[0043] In the present invention, PVA has a good affinity for active materials used in power storage devices, such as carbon materials, metals, and metal oxides. Therefore, when used as a binder, an electrode with high peel strength can be obtained.
[0044] The saponification degree of PVA is preferably 60.0 mol% or more and 99.9 mol% or less, more preferably 65.0 mol% or more and 99.9 mol% or less, further preferably 82.0 mol% or more and 99.0 mol% or less, and particularly preferably 85.0 mol% or more and 95.0 mol% or less. By making the saponification degree within the above range, there is a tendency that practical properties such as peel strength are better and the amount of water-insoluble components is less. The saponification degree of PVA can be measured according to the method described in JIS K 6726 (1994).
[0045] The viscosity average degree of polymerization (hereinafter sometimes referred to as "degree of polymerization") of PVA is not particularly limited, but is preferably 100 to 5000, more preferably 150 to 4500, and even more preferably 200 to 4000. The degree of polymerization of PVA can be measured by the method described in JIS K 6726 (1994).
[0046] The amount of insoluble components when PVA is prepared at 90°C in an aqueous solution with a concentration of 5% by mass (hereinafter sometimes referred to as "water-insoluble components") is preferably 0.1 ppm or more and less than 3000 ppm. The amount of water-insoluble components is more preferably 0.1 ppm or more and 2000 ppm or less, further preferably 0.1 ppm or more and 1000 ppm or less, further preferably 0.1 ppm or more and 500 ppm or less, and particularly preferably 0.1 ppm or more and 100 ppm or less. By making the amount of water-insoluble components within the aforementioned range, the peel strength when used as an adhesive is more excellent. It should be noted that in this specification, ppm refers to mass ppm.
[0047] The amount of insoluble components (water-insoluble components) when preparing an aqueous solution with a concentration of 5% by mass at 90°C is determined by the following method. Prepare a 500mL flask equipped with a stirrer and a reflux condenser in a water bath set to 20°C, add 285g of distilled water to the flask, and start stirring at 300rpm. Weigh 15g of PVA and slowly add the PVA to the flask. After all the PVA (15g) is added, it takes about 30 minutes to raise the temperature of the water bath to 90°C, thereby dissolving the PVA and obtaining a PVA solution. After the temperature of the water bath reaches 90°C, continue to dissolve while stirring at 300rpm for 60 minutes. Thereafter, use the PVA solution to filter out the undissolved and residual PVA particles (hereinafter also referred to as "undissolved particles") using a metal filter with a mesh size of 63μm. Next, the filter was thoroughly washed with warm water at 90°C to remove the PVA solution attached to the filter. After only the undissolved particles remained on the filter, the filter was dried in a heating dryer at 120°C for 1 hour. The mass of the filter after drying was compared with the mass of the filter before filtration to calculate the mass of the undissolved particles. The mass ppm of the undissolved particles relative to the total amount of PVA used to prepare the PVA aqueous solution was set as the amount of insoluble components when preparing an aqueous solution with a concentration of 5% by mass at 90°C.
[0048] From the viewpoint of obtaining an electrode having lower resistance, the PVA is preferably a modified PVA having a structural unit derived from an ethylenically unsaturated dicarboxylic acid-based monomer.
[0049] The content (X) of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer in the modified PVA is preferably 0.01 mol% or more and 10 mol% or less, more preferably 0.1 mol% or more and 5.0 mol% or less, and further preferably 0.2 mol% or more and 2.0 mol% or less. By making the content (X) of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer in the above-mentioned range, there is a tendency that the peel strength when used as a binder is better, and in addition, it is possible to inhibit the modified PVA powder from bonding to each other and forming a block due to moisture in the air, and the operability is improved. In addition, it is also possible to further inhibit the formation of insoluble components in water. In this specification, the content (X) of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer in the modified PVA is sometimes referred to as "modification amount (X)". It should be noted that the modification amount (X) refers to the ratio of the number of moles of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer to the total number of moles of the structural unit constituting the main chain of the modified PVA. The modification amount (X) can be determined by the modified vinyl ester polymer before saponification of the modified PVA. 1 Calculated by H-NMR analysis.
[0050] The ethylenically unsaturated dicarboxylic acid monomer is not particularly limited. In the present application, the ethylenically unsaturated dicarboxylic acid monomer refers to an ethylenically unsaturated dicarboxylic acid and its derivatives. As the derivative of the ethylenically unsaturated dicarboxylic acid, preferably the monoester of the ethylenically unsaturated dicarboxylic acid, the diester of the ethylenically unsaturated dicarboxylic acid or the anhydride of the ethylenically unsaturated dicarboxylic acid. As the ethylenically unsaturated dicarboxylic acid monomer, preferably the monoester of the ethylenically unsaturated dicarboxylic acid, the diester of the ethylenically unsaturated dicarboxylic acid or the anhydride of the ethylenically unsaturated dicarboxylic acid.
[0051] As the ethylenically unsaturated dicarboxylic acid-based monomer, an ethylenically unsaturated dicarboxylic acid, a monoester of an ethylenically unsaturated dicarboxylic acid, a diester of an ethylenically unsaturated dicarboxylic acid, or an anhydride of an ethylenically unsaturated dicarboxylic acid is preferred. Specific examples of the aforementioned ethylenically unsaturated dicarboxylic acid monomers include unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, and itaconic acid; unsaturated dicarboxylic acid monoalkyl esters such as monomethyl maleate, monoethyl maleate, monomethyl fumarate, monoethyl fumarate, monomethyl citraconic acid, monoethyl citraconic acid, monomethyl mesaconic acid, monoethyl mesaconic acid, monomethyl itaconate, and monoethyl itaconate; unsaturated dicarboxylic acid dialkyl esters such as dimethyl maleate, diethyl maleate, dimethyl fumarate, diethyl fumarate, dimethyl citraconic acid, diethyl citraconic acid, dimethyl mesaconic acid, diethyl mesaconic acid, dimethyl itaconate, and diethyl itaconate; and unsaturated dicarboxylic acid anhydrides such as maleic anhydride and citraconic anhydride. From the viewpoint of industrial acquisition and the aspect of reactivity with vinyl ester monomers, maleic acid, monoalkyl maleate, dialkyl maleate, maleic anhydride, monoalkyl fumarate or dialkyl fumarate are sometimes preferred, monoalkyl maleate, dialkyl maleate, maleic anhydride, monoalkyl fumarate or dialkyl fumarate are more preferred, and monomethyl maleate or maleic anhydride are further preferred. The modified PVA may have a structural unit derived from at least one of the aforementioned ethylenically unsaturated dicarboxylic acid monomers, or may have a structural unit derived from two or more ethylenically unsaturated dicarboxylic acid monomers.
[0052] In the modified PVA having a structural unit derived from an ethylenically unsaturated dicarboxylic acid monomer, it is preferred that at least a portion of the structural unit derived from the aforementioned ethylenically unsaturated dicarboxylic acid monomer constitutes a portion of the structural unit represented by the following formula (2). Furthermore, from the aspect of being able to further suppress the amount of water-insoluble components, it is more preferred that the ratio (molar ratio) of the content (Y) of the structural unit represented by formula (2) (hereinafter also referred to as the modification amount (Y)) relative to the content (X) of the structural unit derived from the aforementioned ethylenically unsaturated dicarboxylic acid monomer satisfies the following formula (Q).
[0053] [Chemistry 3]
[0054]
[0055] 0.05≤(Y) / (X)<0.98(Q)
[0056] In formula (2), R 3 R is a hydrogen atom or a linear or branched alkyl group having 1 to 8 carbon atoms. 4 It is a metal atom, a hydrogen atom, or a linear or branched alkyl group having 1 to 8 carbon atoms.
[0057] By making (Y) / (X) satisfy the range shown in the aforementioned formula (Q), it is possible to more easily manufacture a modified PVA with a reduced amount of water-insoluble components industrially. The lower limit of the aforementioned (Y) / (X) is sometimes more preferably 0.06. On the other hand, the upper limit of (Y) / (X) is sometimes more preferably 0.80, further preferably 0.60, and particularly preferably 0.40. It should be noted that the content (Y) of the structural unit shown in formula (2) refers to the ratio of the number of moles of the structural unit of formula (2) to the total number of moles of the structural units constituting the main chain of the modified PVA.
[0058] As R 3 and R 4 The linear or branched alkyl group having 1 to 8 carbon atoms in the group may be, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, 2-methylpropyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, tert-pentyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl (isohexyl) , 1-ethylbutyl, 2-ethylbutyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 1,4-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 3,3-dimethylbutyl, 1-ethyl-2-methyl-propyl, 1,1,2-trimethylpropyl, n-heptyl, 2-methylhexyl, n-octyl, isooctyl, tert-octyl, 2-ethylhexyl, 3-methylheptyl, etc. The number of carbon atoms in the alkyl group is preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 3.
[0059] In R 4 In the invention, the metal atom includes alkali metals such as lithium, sodium, potassium, rubidium, and cesium; and alkaline earth metals such as calcium, barium, strontium, and radium. Among these, alkali metals are sometimes preferred, and lithium or sodium is more preferred.
[0060] When the aforementioned ethylenically unsaturated dicarboxylic acid monomers are used to produce modified PVA, the introduced structural units derived from the ethylenically unsaturated dicarboxylic acid monomers sometimes partially form a six-membered ring lactone ring structure represented by the aforementioned formula (2) after saponification. The six-membered ring lactone structure represented by the aforementioned formula (2) sometimes opens due to heating, and then forms a crosslinked body through an intermolecular esterification reaction. At this time, the amount of water-insoluble components in the modified PVA sometimes increases. That is, if the content (Y) of the structural unit represented by formula (2) is greater than the content (X) of the structural unit derived from the introduced ethylenically unsaturated dicarboxylic acid monomers, it means that the crosslinking reaction is suppressed. It can be considered that the six-membered ring lactone structure of the aforementioned formula (2) is measured using a deuterated dimethyl sulfoxide solvent. 1 It is detected at 6.8 to 7.2 ppm in the H-NMR spectrum. In the aforementioned modified PVA, from the viewpoint of further reducing the amount of water-insoluble components, the content (Y) of the structural unit represented by formula (2) relative to the content (X) of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer obtained from the modified vinyl ester polymer before saponification preferably satisfies the aforementioned formula (Q). It should be noted that when (Y) / (X) in formula (Q) is 0.50, it means that half of all the structural units derived from the ethylenically unsaturated dicarboxylic acid monomer introduced form a part of the structural unit represented by formula (2).
[0061] In one embodiment of the present invention, the shape of PVA is not particularly limited, and sometimes a powdered PVA powder is also preferred. The particle size of the particles constituting the powder is not particularly limited, and sometimes it is preferred that more than 95% by mass of the entire PVA powder will pass through a sieve with a mesh of 1.00 mm, and more preferably more than 95% by mass of the entire PVA powder will pass through a sieve with a mesh of 710 μm. Here, the aforementioned "more than 95% by mass of the entire PVA powder" refers to: as a particle size distribution, for example, the cumulative distribution of more than 95% by mass of particles passing through a sieve with a mesh of 1.00 mm. By making the particles passing through a sieve with a mesh of 1.00 mm more than 95% by mass, it is possible to further suppress uneven drying due to the small particles, and it is easier to control the amount of water-insoluble components. In addition, with respect to the particle size of the particles constituting the PVA powder, the amount passing through a sieve with a mesh of 500 μm is sometimes preferably more than 30% by mass of the entire PVA powder, more preferably 35% by mass, further preferably more than 45% by mass, and particularly preferably more than 56% by mass. Furthermore, regarding the particle size of the particles constituting the PVA powder, it is sometimes preferred that 99% by mass or more of the PVA powder passes through a sieve with a mesh size of 1.00 mm, and more preferably 99% by mass or more of the PVA powder passes through a sieve with a mesh size of 1.00 mm and 56% by mass or more passes through a sieve with a mesh size of 500 μm. The mesh size of the sieve is based on the nominal mesh size W of JIS Z 8801-1 (2006).
[0062] In the binder for the storage device of the present invention, PVA may also preferably have a cross-linked structure. The cross-linked structure may be a structure in which the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer in the PVA is cross-linked between molecules. In addition, the cross-linked structure of PVA may be formed in the storage device binder solution, storage device electrode slurry, storage device electrode and / or storage device described later.
[0063] [Manufacturing method of PVA]
[0064] Hereinafter, a method for producing PVA will be described. It should be noted that the method for producing PVA is not limited to the method described below.
[0065] PVA is produced, for example, by a production method comprising the steps of: polymerizing a vinyl ester monomer to obtain a vinyl ester polymer; saponifying the obtained vinyl ester polymer in an alcohol solution using an alkali catalyst or an acid catalyst; washing; and drying.
[0066] In addition, when the PVA is a modified PVA containing a structural unit derived from an ethylenically unsaturated dicarboxylic acid monomer, it is produced, for example, by a production method having the following steps: a step of copolymerizing an ethylenically unsaturated dicarboxylic acid monomer and a vinyl ester monomer to obtain a modified vinyl ester polymer; a saponification step of saponifying the obtained modified vinyl ester polymer using an alkali catalyst or an acid catalyst in an alcohol solution; a washing step and a drying step.
[0067] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate, and vinyl acetate is preferred.
[0068] As a method for polymerizing vinyl ester monomers, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. Among the methods, bulk polymerization under solvent-free conditions or solution polymerization using a solvent such as alcohol is generally used. From the viewpoint of improving the effect of the present invention, a solution polymerization method polymerized with lower alcohols such as methanol is preferred. When the polymerization reaction is carried out by bulk polymerization or solution polymerization, the reaction method can also use any method of intermittent and continuous methods. In addition, when a monomer other than a vinyl ester monomer such as an ethylenically unsaturated dicarboxylic acid monomer is copolymerized with a vinyl ester monomer, the aforementioned method is also preferred.
[0069] The initiator used in the polymerization reaction is not particularly limited as long as it does not impair the effect of the present invention, and examples thereof include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile); and known initiators such as organic peroxide initiators such as benzoyl peroxide and n-propyl peroxycarbonate. The polymerization temperature during the polymerization reaction is not particularly limited and may be in the range of 5 to 200°C or in the range of 30 to 150°C.
[0070] As long as the effects of the present invention are not impaired, other copolymerizable monomers other than vinyl ester monomers may be further copolymerized as needed. For example, as described above, ethylenically unsaturated dicarboxylic acid monomers and vinyl ester monomers may be copolymerized. In addition, other copolymerizable monomers other than ethylenically unsaturated dicarboxylic acid monomers and vinyl ester monomers may be further copolymerized. Examples of monomers other than ethylenically unsaturated dicarboxylic acid monomers and vinyl ester monomers include α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; acrylamide monomers such as acrylamide, N-methylacrylamide, and N-ethylacrylamide; methacrylamide monomers such as methacrylamide, N-methylmethacrylamide, and N-ethylmethacrylamide; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, and n-butyl vinyl ether; hydroxyl-containing vinyl ether monomers such as ethylene glycol vinyl ether, 1,3-propylene glycol vinyl ether, and 1,4-butanediol vinyl ether; allyl ether monomers such as propyl allyl ether, butyl allyl ether, and hexyl allyl ether; Monomers having a silyl group; α-olefins containing hydroxyl groups such as isopropenyl acetate, 3-butene-1-ol, 4-pentene-1-ol, 5-hexene-1-ol, 7-octen-1-ol, 9-decen-1-ol, and 3-methyl-3-butene-1-ol; monomers having a silyl group such as vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyldimethylmethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldimethylethoxysilane, 3-(methyl)acrylamide-propyltrimethoxysilane, and 3-(methyl)acrylamide-propyltriethoxysilane; N-vinylamide monomers such as N-vinylformamide, N-vinylacetamide, N-vinyl-2-pyrrolidone, and N-vinyl-2-caprolactam. The amount of monomers other than the ethylenically unsaturated dicarboxylic acid monomers and the vinyl ester monomers used also varies depending on their purpose and application, but is usually 10 mol% or less, sometimes preferably 5.0 mol% or less, more preferably 3.0 mol% or less, and further preferably 2.0 mol% or less, based on the ratio of all monomers used for copolymerization.
[0071] The vinyl ester polymer obtained in the above-mentioned polymerization step is subjected to a saponification step in an alcohol solvent, a washing step, and a drying step to obtain PVA. The saponification conditions and drying conditions for obtaining PVA are not particularly limited, but from the perspective of being able to suppress the amount of water-insoluble components of PVA, it is preferred that the water content of the saponification raw material solution, the temperature of the PVA resin during drying, or the drying time be set to a specific range.
[0072] A saponification raw material solution can be prepared by further adding a small amount of water to the solution containing the vinyl ester polymer and the solvent obtained in the above-mentioned polymerization step. The amount of water added is preferably adjusted in such a way that the water content (also referred to as "system water content") of the obtained saponification raw material solution exceeds 1.0 mass % and is less than 5.0 mass %. The water content is sometimes more preferably 1.5 to 4.0 mass %. By making the water content within the above-mentioned range, the base catalyst can be further suppressed from acting as a catalyst for crosslinking, the content of the components insoluble in water during drying can be more easily controlled, and the saponification reaction rate can be made better.
[0073] As solvents that can be used in the saponification reaction, methanol, ethanol, isopropanol, etc. can be listed. They can be used alone or in combination of two or more. In addition, it can be a mixed solvent in which esters such as methyl acetate coexist within the range that does not affect the saponification reaction process. Among these solvents, methanol or a mixed solvent of methanol and methyl acetate is preferably used.
[0074] As a catalyst for the saponification reaction of the vinyl ester polymer, an alkali catalyst is generally used. Examples of the alkali catalyst include alkali metal hydroxides such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; and alkali metal alkoxides such as sodium methoxide, preferably sodium hydroxide. The amount of the catalyst used is preferably 0.005 to 0.50, more preferably 0.008 to 0.40, and further preferably 0.01 to 0.30 in terms of the molar ratio of the vinyl ester unit of the vinyl ester polymer. The catalyst may be added all at once at the beginning of the saponification reaction, or a portion may be added at the beginning of the saponification reaction, and the remainder may be added in the middle of the saponification reaction.
[0075] The temperature of the saponification reaction is sometimes preferably in the range of 5 to 80° C., more preferably in the range of 20 to 70° C. The time of the saponification reaction is sometimes preferably in the range of 5 minutes to 10 hours, more preferably in the range of 10 minutes to 5 hours. The saponification reaction can be carried out in any of a batch process and a continuous process. When an alkali catalyst is used for the saponification reaction, in order to stop the saponification reaction, an acid such as acetic acid and lactic acid can be added as needed to neutralize the residual catalyst. Among them, after neutralization, it is easy to carry out a cross-linking reaction between the molecules of PVA during drying due to the residual acid. Therefore, from the viewpoint of suppressing the amount of water-insoluble components to control it, it is preferably not neutralized by adding such an acid.
[0076] The method of saponification reaction is not particularly limited as long as it is a known method. For example, the following methods can be listed: (1) a method of mixing a solution of a modified vinyl ester polymer adjusted to a concentration of more than 20% by mass and a catalyst, and crushing the resulting semi-solid (gel-like substance) or solid with a grinder to obtain PVA powder; (2) a method of suppressing the overall reaction solution from presenting a non-fluid gel state by controlling the concentration of the modified vinyl ester polymer dissolved in a solvent containing an alcohol (preferably methanol) to less than 10% by mass, so that the PVA is precipitated in the solvent and obtained in the form of microparticles dispersed in methanol; (3) a method of adding a saturated hydrocarbon solvent, emulsifying the vinyl ester polymer or saponifying it in a suspended phase to obtain PVA. In the above (1), the grinder is not particularly limited, and a known grinder or crusher can be used. From the perspective of manufacturing, method (1) or method (2) that does not require a saturated hydrocarbon solvent is preferred. The method (2) is also preferred from the viewpoint that even when the subsequent washing step and drying step are performed at weaker temperatures than conventional methods, the water-insoluble component can be reduced to a trace amount, which is industrially advantageous.
[0077] From the viewpoint of being able to reduce the water-insoluble components in the obtained PVA, it is preferred to set a step of washing the PVA as needed after the saponification step. As a cleaning liquid, a solution containing a lower alcohol such as methanol as the main component and also containing water and / or an ester such as methyl acetate can be used. As a cleaning liquid, a solution containing methanol as the main component and methyl acetate is preferred. When methanol suitable for use in the copolymerization step of vinyl ester polymers and methyl acetate generated in the saponification step are used as cleaning liquids, they can be reused within the process without preparing other solvents as cleaning liquids, which is preferred in terms of economy and process. In order to reduce the amount of water-insoluble components in the obtained PVA, the content of methyl acetate is sometimes preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 70% by volume or more.
[0078] After the saponification step or the washing step, the polymer can be dried to obtain a powdered PVA. Specifically, hot air drying using a drum dryer is preferred, and the temperature of the PVA during drying is sometimes preferably greater than 80°C and less than 120°C, more preferably greater than 90°C and less than 110°C. In addition, the drying time is sometimes preferably 2 to 10 hours, more preferably 3 to 8 hours. By setting the drying conditions to the above range, it is easier to suppress the amount of water-insoluble components present in the obtained PVA.
[0079] As one of the embodiments of the present invention, the binder for power storage devices may include more than two kinds of PVA. For example, the binder for power storage devices may include a modified PVA (A1) and other PVA (A2) containing a structural unit derived from an ethylenically unsaturated dicarboxylic acid monomer. The content of PVA (A2) can be 0% by mass or more and 70% by mass or less relative to the total amount of the modified PVA (A1) and PVA (A2). The upper limit of the content of the PVA (A2) is sometimes preferably 60% by mass, more preferably 50% by mass, further preferably 40% by mass, further preferably 20% by mass, and particularly preferably 10% by mass. In addition, the content of PVA (A2) can be 0% by mass, that is, the PVA in the binder for power storage devices can all be modified PVA (A1). The viscosity average polymerization degree of PVA (A2) is not particularly limited, for example, it can be 100 or more and 5000 or less, sometimes preferably 200 or more and 3000 or less, and more preferably 400 or more and 2000 or less. In addition, the viscosity average degree of polymerization of PVA (A2) is preferably less than the viscosity average degree of polymerization of the aforementioned modified PVA (A1). The viscosity average degree of polymerization of PVA (A2) can be measured according to the method described in JIS K 6726 (1994). In addition, the saponification degree of PVA (A2) can be greater than 80.0 mol % and less than 99.9 mol %. The saponification degree of PVA (A2) can be measured according to the method described in JIS K 6726 (1994). In addition, PVA (A2) may be modified.
[0080] In the present invention, PVA is preferably dissolved at a solid content concentration of 7.5% by mass or more relative to N-methyl-2-pyrrolidone under heating and stirring conditions of 90°C for 2 hours. In this case, the affinity for carbon materials such as graphite is improved, and the adhesion and coating properties are good. Sometimes, it can further dissolve at 8.0% by mass or more, and further dissolve at 8.5% by mass or more.
[0081] [Compound represented by formula (1)]
[0082] In the present invention, the binder for an electrical storage device contains, in addition to the above-mentioned PVA, a compound represented by the following formula (1) (hereinafter sometimes referred to as "compound (1)").
[0083] [Chemistry 4]
[0084]
[0085] In formula (1), R 1 and R 2 Each of the two R in formula (1) is independently an alkyl group having 1 to 4 carbon atoms. 1 can be the same or different. Similarly, the two R in formula (1) 2 can be the same or different. Wherein, the two R in formula (1) 1 The two R in formula (1) are preferably the same. 2 Also preferably the same. 1 It is preferably an alkyl group having 1 to 2 carbon atoms, and more preferably a methyl group. 2 An alkyl group having 2 to 4 carbon atoms is preferred, an alkyl group having 3 to 4 carbon atoms is more preferred, an alkyl group having 4 carbon atoms is further preferred, and an isobutyl group is particularly preferred.
[0086] m and n are each independently an integer of 0 to 25. At least one of m and n is preferably 1 or more.
[0087] By making compound (1) have the above-mentioned structure, the affinity with PVA and the surface of the active material is improved, so that compound (1) exists in PVA with high uniformity, and the effect of reducing resistance can be obtained. In addition, when making slurry, the active material is dispersed together with PVA and foaming is suppressed, so that a highly uniform electrode can be obtained.
[0088] From the above viewpoints, it is preferred that R in formula (1) 1 Methyl, R 2 isobutyl, and m and n are each an integer less than 8. Compound (1) may be composed of only one species or a mixture of two or more species. In compound (1) composed of one species or two or more species, the average value of the sum of m and n (m+n) is preferably 1 or more, more preferably 3 or more, and even more preferably 5 or more. In addition, the average value of m+n is preferably 50 or less, more preferably 30 or less, and even more preferably 25 or less.
[0089] The mass ratio of PVA to compound (1) is sometimes preferably 60:40 to 99:1, more preferably 80:20 to 95:5, and further preferably 85:15 to 90:10. By being in the aforementioned range, there is a tendency that the foaming of the slurry during the preparation of the slurry can be suppressed, the adhesion becomes higher, and the electrode is less likely to be damaged when cutting, and the ion conductivity is improved and the resistance becomes lower. In addition, when the binder for storage devices contains modified PVA (A1), the mass ratio of modified PVA (A1) to compound (1) can be 60:40 to 99:1, and sometimes preferably 80:20 to 95:5, and more preferably 85:15 to 90:10.
[0090] Examples of methods for adding compound (1) include: adding in the form of a liquid, adding in a state where it is mixed with other substances such as an active substance, adding in the form of a solution of compound (1), adding in a state where compound (1) coexists in the aforementioned PVA or its solution, etc. These methods of adding are not particularly limited.
[0091] In the present invention, the binder may also contain a material for adjusting the viscosity of the binder in an aqueous solution state or in a solution state of N-methyl-2-pyrrolidone (NMP). As materials for adjusting the viscosity, inorganic substances such as polyacids and salts thereof, condensates thereof, fused silica, and alumina such as citric acid, tartaric acid, and aspartic acid may be cited. Their addition amount is not particularly limited, and relative to the total amount of 100 parts by mass of PVA and compound (1), it is sometimes preferably 0.01 parts by mass and 10 parts by mass or less, more preferably 0.02 parts by mass and 8 parts by mass or less, and further preferably 0.05 parts by mass and 5 parts by mass or less. By making the addition amount of the material for adjusting the viscosity the aforementioned range, the viscosity of the binder in a solution state can be further increased, and it can be more easily adjusted to within a specified range. In addition, there is a tendency that the more inorganic substances contain substances with smaller particle sizes, the easier it is to increase the viscosity of the binder in an aqueous solution state or in a solution state of NMP.
[0092] In the present invention, the binder for storage device or the binder solution for storage device described later can further contain a compounding agent within the range of not damaging the effect of the present invention. As a compounding agent, for example, a light stabilizer, an ultraviolet absorber, a freezing stabilizer, a thickener, a leveling agent, a rheological stabilizer, a thixotropic agent, a defoamer, a plasticizer, a lubricant, a preservative, a rust inhibitor, an antistatic agent, an antistatic agent, an anti-yellowing agent, a pH adjuster, a film-forming aid, a curing catalyst, a cross-linking reaction catalyst, a cross-linking agent (glyoxal, urea resin, melamine resin, polyvalent metal salt, polyisocyanate, polyamide epichlorohydrin, etc.), a dispersant, etc. can be listed. The compounding agent can be selected or combined according to each purpose to be mixed. The content of the compounding agent is, for example, sometimes 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, according to the total amount of PVA and compound (1) or the total amount of the binder solution for storage device.
[0093] In one embodiment of the present invention, the binder for a storage device may be a solid, specifically a powder. In the case of a powder, it may be a mixture of powders of each component (PVA, compound (1), etc.), or it may be a powder containing multiple components in one particle. In the present invention, the binder for a storage device may be obtained by dissolving the above-mentioned PVA and compound (1) and other components contained as required in a solvent to form a solution, and removing the solvent. Here, as a solvent, water and NMP are suitable. In addition, the solution may also be directly used as a storage device binder solution described later, and subsequently used to prepare a storage device electrode slurry. The components of the storage device binder, namely PVA and compound (1), may be pre-mixed before preparing the storage device electrode slurry. In addition, when preparing the storage device electrode slurry, PVA and compound (1) may be added and mixed at the same time or at different times, and the storage device electrode slurry prepared in this way contains the storage device binder of the present invention. In addition, the binder of the present invention is contained in a state mixed with components such as active materials in the solidified body of the storage device electrode slurry.
[0094] <Binder solution for electrical storage devices>
[0095] By dissolving the binder for the storage device of the present invention in at least one solvent, a binder solution for storage device (hereinafter also referred to as "binder solution") is obtained, which is also a mode of the present invention. The binder solution for storage device according to one embodiment of the present invention only needs to contain the binder for storage device according to one embodiment of the present invention and a solvent. The solvent is not particularly limited, and is preferably water or NMP. When the solvent is water, it is suitable from the viewpoint of reducing the environmental burden and the simplicity of the equipment. On the other hand, when the solvent is NMP, especially when used as a slurry for the positive electrode, the active material in the slurry is not easy to deteriorate, so it is suitable.
[0096] In addition to the binder of the present invention, the binder solution may contain an additive (referred to as additive F) that is soluble in the solvent within a range that does not impair the effects of the present invention. Examples of additive F include polyethylene glycol, polyethylene glycol dimethyl ether, polyethylene glycol diglycidyl ether, polyethyleneimine, and the like. The content of additive F is, for example, 10% by mass or less, and is sometimes preferably 5% by mass or less, and more preferably 1% by mass or less, depending on the total amount of the binder solution. In addition, it is sometimes preferred that additive F is not contained.
[0097] The binder solution is obtained by mixing the binder of the present invention, water, solvents such as NMP, and the aforementioned additives optionally included as required, etc., using a known method, such as stirring. The mixing temperature and mixing time can be appropriately adjusted according to the type of solvent. It should be noted that in the binder solution, the mass of the binder dissolved in the solvent is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, further preferably 99% by mass or more, and particularly preferably 100% by mass, in other words, it is particularly preferred that the binder is substantially completely dissolved.
[0098] In the present invention, the content of the binder in the binder solution is preferably 1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 20% by mass or less, and further preferably 5% by mass or more and 15% by mass or less, depending on the total amount of the binder solution. If the content of the binder is 1% by mass or more, it is easier to improve the adhesion of the active material to the collector when forming the electrode. If the content of the binder is 30% by mass or less, it is possible to further suppress the rapid aggregation of the active material when forming the electrode. In addition, as a preferred embodiment, in the binder solution, the total content of PVA and compound (1) can be the aforementioned range according to the total amount of the binder solution.
[0099] <Electrode slurry for power storage devices>
[0100] The electrical storage device electrode slurry of the present invention contains the electrical storage device binder solution of the present invention and an active material.
[0101] The storage device electrode slurry of the present invention can be used for any electrode of the positive electrode and the negative electrode. In addition, it can be used for both the positive electrode and the negative electrode. Therefore, the active material can be any one of the positive electrode active material and the negative electrode active material. As a preferred embodiment, when the binder solution of the present invention contains water (when the solvent is water), it contains the negative electrode active material and is used in the form of a slurry for the negative electrode. In addition, as a preferred embodiment, when the binder solution of the present invention contains NMP (when the solvent is NMP), it contains the positive electrode active material and is used in the form of a slurry for the positive electrode.
[0102] The negative electrode active material may be a material that has been used as a negative electrode active material for a power storage device. Examples thereof include carbon materials such as amorphous carbon, artificial graphite, natural graphite (graphite), mesocarbon microbeads (MCMB), pitch-based carbon fibers, carbon black, activated carbon, carbon fibers, hard carbon, soft carbon, mesoporous carbon, and conductive polymers such as polyacene; silicon (Si) and silicon compounds (SiO x ) and other silicon-based materials; composite materials of silicon-based materials and carbon materials (Si / C or SiO x / C)、SnO x and LiTiO x The composite metal oxides shown, other metal oxides, lithium metals, lithium alloys and other lithium-based metals; metal compounds such as TiS2 and LiTiS2; and composite materials of metal oxides and carbon materials. Among these, from the perspective of economy and battery capacity, carbon materials (graphite, etc.), silicon-based materials, or composite materials of silicon-based materials and carbon materials are preferred. These negative electrode active materials can be used alone or in combination of two or more.
[0103] The positive electrode active material may be a material that has been used as a positive electrode active material for a power storage device. Examples thereof include TiS2, TiS3, amorphous MoS3, Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O. 13 Transition metal oxides such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi x Co y Mo z O2 and LiFePO4, LiMn 1-x Fe x PO4 and other lithium-containing composite metal oxides; and sulfur compounds such as sulfur elements, organic sulfur compounds or mixtures thereof. These positive electrode active materials can be used alone or in combination of two or more. It should be noted that the above x, y, and z represent composition ratios.
[0104] The electrical storage device electrode slurry may include a conductive aid (conductive imparting agent). The conductive aid is used to enable the electrical storage device to achieve high output, and can be appropriately selected according to the situation for the positive electrode or the negative electrode. As an example thereof, for example, graphite, acetylene black, carbon black, Ketjen black, vapor-grown carbon fiber, etc. can be cited. From the viewpoint that the obtained electrical storage device is more easily high-output, among these, acetylene black is preferably used.
[0105] When the storage device electrode slurry contains a conductive auxiliary agent, the content of the conductive auxiliary agent is preferably 0.1 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the active material. If the content of the conductive auxiliary agent is within this range, the reduction in battery capacity to which the slurry is applied can be further suppressed, and a more excellent conductive auxiliary effect can be obtained.
[0106] The content of the binder in the storage device electrode slurry is preferably 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material. If the content is 0.1 parts by mass or more, the adhesion of the active material to the collector is improved, which is more advantageous from the viewpoint of maintaining the durability of the applied battery. Furthermore, if the content is 20 parts by mass or less, it is easier to increase the discharge capacity. From this viewpoint, the range of the content is sometimes more preferably 0.2 parts by mass or more and 18 parts by mass or less, more preferably 0.5 parts by mass or more and 16 parts by mass or less, and more preferably 1 part by mass or more and 12 parts by mass or less. In addition, as a preferred embodiment, in the storage device electrode slurry, the total content of PVA and compound (1) relative to 100 parts by mass of the active material can be the aforementioned range.
[0107] In addition to the binder, active material, conductive additive and solvent, the storage device electrode slurry may also contain additives such as flame retardant additives, thickeners, defoamers, leveling agents, and adhesion imparting agents as needed. As thickeners, polysaccharides such as carboxymethyl cellulose (CMC) and their salts can be listed. In the case of including these additives, the content of the additives is preferably 0.1% by mass or more and 10% by mass or less according to the total amount of the slurry.
[0108] In the storage device electrode slurry, the content of PVA relative to the total polymer components is preferably 20% by mass or more, more preferably 40% by mass or more. In this case, the function of PVA as a binder is more fully exerted. The content of PVA relative to the total polymer components can be 100% by mass or less, 80% by mass or less, or 60% by mass or less.
[0109] In the storage device electrode slurry, the content of the water-soluble polymer (such as PVA, CMC, etc.) relative to the total polymer components is preferably 50% by mass or more, more preferably 70% by mass or more. In this embodiment, water is preferably included in the form of a solvent. In this case, the adhesion of the active material to the collector is further improved. The content of the water-soluble polymer relative to the total polymer components can be 100% by mass or less. In this embodiment, the storage device electrode slurry can be a negative electrode slurry.
[0110] The electrical storage device electrode slurry can be obtained by mixing a binder, an active material, and, if necessary, a conductive auxiliary agent, a solvent, and additives by a conventional method using a mixer such as a planetary mixer, a ball mill, a blending mill, or a triple roll mill.
[0111] <Electrode for power storage device>
[0112] The electric storage device electrode of the present invention comprises a solidified body of the electric storage device electrode slurry and a current collector. The solidified body of the electric storage device electrode slurry is a solidified product obtained by removing the solvent in the electric storage device electrode slurry by drying or the like. That is, in this specification, the solidified body is not limited to a substance solidified by a chemical reaction such as a cross-linking reaction, as long as it is a substance after the solvent is removed by drying or the like. In other words, the solidified body can be a dried body or a solid body.
[0113] The storage device electrode of the present invention can be either a positive electrode or a negative electrode. In the electrode of the present invention, the active material has excellent adhesion to the collector. Therefore, the peel strength of the electrode (peel strength between the collector and the solidified body) is preferably 200N / m or more, more preferably 300N / m or more, further preferably 400N / m or more, and further preferably 450N / m or more before the electrolyte is impregnated. It should be noted that the upper limit of the peel strength of the electrode can be 1000N / m. If the peel strength of the electrode is in the aforementioned range, the active material is less likely to peel off from the collector, and the precipitation and short circuit of lithium, etc. during the charge and discharge of the electrode can be suppressed. In addition, if the peel strength is in the aforementioned range, the active material is less likely to peel off from the collector when the electrode is punched or cut, which is suitable.
[0114] The electrical storage device electrode of the present invention can be obtained, for example, by applying the electrical storage device electrode slurry of the present invention to a current collector and removing the solvent by drying, etc. In addition, the electrode may be subjected to a rolling treatment after drying.
[0115] The current collector is not particularly limited as long as it is made of a conductive material. Examples include metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum. These current collectors can be used alone or in combination of two or more. Among the current collectors, from the viewpoint of the adhesion of the active material and the discharge capacity, copper is preferably used as the negative electrode current collector, and aluminum is preferably used as the positive electrode current collector.
[0116] The method for applying the slurry to the current collector is not particularly limited, and examples thereof include an extrusion coater, a reverse roll, a doctor blade, an applicator, etc. The amount of the slurry applied is appropriately selected depending on the desired thickness of a cured product derived from the slurry composition.
[0117] Examples of the rolling method for the electrical storage device electrode include die pressing, roll pressing, etc. The pressing pressure is preferably 1 MPa to 40 MPa from the viewpoint of making it easier to increase the battery capacity.
[0118] In the storage device electrode, the collector may be a plate-shaped member. The thickness of the collector is sometimes preferably 1 μm or more and 20 μm or less, more preferably 2 μm or more and 15 μm or less. In the storage device electrode, the solidified body of the storage device electrode slurry may be a layer directly laminated on the collector or laminated on the collector with the aid of other layers. The thickness of the solidified body of the storage device electrode slurry is sometimes preferably 10 μm or more and 400 μm, more preferably 20 μm or more and 300 μm. In the present invention, the thickness of the storage device electrode is preferably 20 μm or more and 200 μm.
[0119] <Electrical Storage Equipment>
[0120] The electrical storage device of the present invention includes the electrical storage device electrode. The electrical storage device electrode in the electrical storage device may be either a negative electrode or a positive electrode, or may be both a negative electrode and a positive electrode.
[0121] The power storage device may be a battery, and examples thereof include lithium ion secondary batteries, sodium ion batteries, lithium sulfur batteries, all-solid-state batteries, lithium ion capacitors, lithium batteries, nickel hydrogen batteries, and alkaline dry batteries.
[0122] The power storage device may include an electrolyte. Here, the electrolyte is a solution obtained by dissolving an electrolyte in a solvent. The electrolyte may be in a liquid or gel state as long as it is an electrolyte commonly used in power storage devices, and a substance that functions as a battery may be appropriately selected according to the types of negative electrode active materials and positive electrode active materials. As a specific electrolyte, for example, well-known lithium salts may be suitably used, and examples thereof include LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10, LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lower aliphatic lithium carboxylates, etc.
[0123] The solvent contained in the electrolyte is not particularly limited. Specific examples thereof include carbonates such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and vinylene carbonate; lactones such as γ-butyrolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; sulfoxides such as dimethyl sulfoxide; oxetanes such as 1,3-dioxolane and 4-methyl-1,3-dioxolane (oxetanes) xolane); nitrogen-containing compounds such as acetonitrile and nitromethane; organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate and ethyl propionate; inorganic acid esters such as triethyl phosphate, dimethyl carbonate and diethyl carbonate; diethylene glycol dimethyl ether and triethylene glycol dimethyl ether; oxazolidinones such as cyclopentane and 3-methyl-2-oxazolidinone; sultones such as 1,3-propane sultone, and 1,4-butane sultone and naphthalene sultone, etc. They can be used alone or in combination of two or more. When using a gel-like electrolyte, a nitrile polymer, an acrylic polymer, a fluorine polymer, an alkylene oxide polymer, etc. can be added as a gelling agent.
[0124] In the electric storage device of the present invention, when the electric storage device electrode is used for either the positive electrode or the negative electrode, a known or commonly used electrode may be used as an electrode not using the electric storage device electrode (ie, an electrode not containing the electric storage device binder).
[0125] In a preferred embodiment, the electrical storage device includes the aforementioned electrical storage device electrode as a negative electrode, and includes a known or commonly used electrode as a positive electrode. That is, in a preferred embodiment of the present invention, the electrical storage device includes a negative electrode including the aforementioned electrical storage device binder and a positive electrode not including the aforementioned electrical storage device binder. In this case, the positive electrode is not particularly limited as long as it is a positive electrode commonly used in electrical storage devices.
[0126] Alternatively, in another preferred embodiment, the power storage device includes the power storage device electrode of the present invention as a positive electrode, and includes a known or customary electrode as a negative electrode. That is, in a preferred embodiment, the power storage device has a positive electrode including the aforementioned power storage device binder and a negative electrode not containing the aforementioned power storage device binder. The negative electrode is not particularly limited as long as it is a negative electrode commonly used in power storage devices. In this case, the binder solution contained in the power storage device electrode slurry used when forming the positive electrode is preferably a binder solution containing the binder of the present invention and N-methyl-2-pyrrolidone (NMP). This is because: by making the solvent in the power storage device electrode slurry NMP, the degradation of the positive electrode active material in the power storage device electrode slurry can be suppressed, and according to the characteristics of the aforementioned PVA contained in the binder, the peel strength of the positive electrode can be improved.
[0127] In addition, both the positive electrode and the negative electrode may be the electrical storage device electrodes of the present invention. That is, in a preferred embodiment of the present invention, the electrical storage device includes a positive electrode containing the electrical storage device binder and a negative electrode containing the electrical storage device binder.
[0128] As a method for manufacturing an electrical storage device, there is no particular limitation. For example, when the electrical storage device is a battery, it can be manufactured as follows. That is, the negative electrode and the positive electrode can be overlapped through a separator such as a polypropylene porous film, and can be rolled and / or folded according to the shape of the battery, put into a battery container, and an electrolyte is injected and sealed. The shape of the battery can be any of the known coin type, button type, sheet type, cylindrical type, square type, flat type, etc.
[0129] In the present invention, the power storage device is useful in various applications. For example, it is also useful as a battery used in a portable terminal that requires miniaturization, thinning, lightness, and high performance. In addition, it can also be suitably used in batteries for devices that require flexibility, such as wound dry batteries and laminated batteries.
[0130] Example
[0131] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited thereto. The % in the embodiments refers to mass unless otherwise specified. First, the measurement method and the evaluation method are shown below. It should be noted that the physical property values (or evaluation values) recorded in this specification are based on the values obtained by the following methods.
[0132] The physical properties of each PVA used in each of the examples and comparative examples described below, the evaluation of the aqueous binder solution and NMP solution containing the PVA, the evaluation in electrode application, and the evaluation in battery application were measured according to the following methods.
[0133] [Viscosity average degree of polymerization of PVA]
[0134] The viscosity average degree of polymerization of PVA is measured in accordance with JIS K 6726 (1994). Specifically, when the saponification degree of PVA is less than 99.5 mol%, the PVA is saponified until the saponification degree reaches 99.5 mol% or more, and the viscosity average degree of polymerization (P) is calculated using the following formula using the intrinsic viscosity [η] (liter / g) measured in water at 30°C for the obtained PVA.
[0135] P=([η]×10 4 / 8.29) (1 / 0.62)
[0136] [Saponification degree of PVA]
[0137] The saponification degree of PVA is determined by the method described in JIS K 6726 (1994).
[0138] [Modification amount (X)]
[0139] The content (X) of the structural unit derived from the ethylenically unsaturated dicarboxylic acid monomer in the modified PVA (modification amount (X)) is determined by 1 H-NMR spectrum analysis was calculated from the spectrum of the modified species.
[0140] [Content (Y) of the structural unit represented by formula (2)]
[0141] The content (Y) of the structural unit represented by formula (2) in the modified PVA (modification amount (Y)) is measured using dimethyl sulfoxide solvent. 1 The amount of modification (Y) was calculated from the spectrum detected at 6.8 to 7.2 ppm in H-NMR spectrum analysis. Also, (Y) / (X) was calculated from the ratio of the amount of modification (Y) to the amount of modification (X).
[0142] [Amount of insoluble components when an aqueous solution having a concentration of 5% by mass is prepared at 90° C. (amount of water-insoluble components)]
[0143] Prepare a 500mL flask equipped with a stirrer and a reflux condenser in a water bath set to 20°C, add 285g of distilled water to the flask, and start stirring at 300rpm. Weigh 15g of PVA powder and slowly add the PVA powder to the flask. After all the PVA powder (15g) is added, it takes about 30 minutes to raise the temperature of the water bath to 90°C, thereby dissolving the PVA powder and obtaining a PVA solution. After the temperature of the water bath reaches 90°C, continue to dissolve while stirring at 300rpm for 60 minutes. Thereafter, use the above-mentioned PVA solution to filter the undissolved and remaining particles (undissolved particles) using a metal filter with a mesh of 63μm. Next, the filter is thoroughly cleaned with 90°C warm water to remove the solution attached to the filter. After only undissolved particles remain on the filter, the filter is dried in a heating dryer at 120°C for 1 hour. The mass of the dried filter is compared with the mass of the filter before filtration to calculate the mass of the undissolved particles. The ratio of the mass of the undissolved particles to the total amount of PVA used to prepare the PVA solution was defined as the amount of insoluble components (water-insoluble content) when a 5 mass % aqueous solution was prepared at 90°C.
[0144] [Particle size distribution]
[0145] The particle size distribution of PVA powder was determined using the dry sieving method described in JIS Z 8815 (1994). PVA powder was placed on a sieve (filter) with a mesh size of 1.00 mm, the mass of the PVA powder that passed the sieve was measured, and the proportion (mass %) of PVA particles that passed the sieve was calculated based on the mass of the PVA powder before sieving. Similarly, independently of the sieve with a mesh size of 1.00 mm, PVA powder was placed on a sieve (filter) with a mesh size of 500 μm, the mass of the PVA powder that passed the sieve was measured, and the proportion (mass %) of PVA particles that passed the sieve was calculated based on the mass of the PVA powder before sieving. It should be noted that the aforementioned mesh size is based on the nominal mesh size W of JIS Z 8801-1 (2006).
[0146] <Appearance (anti-foaming) evaluation of coating film>
[0147] Immediately after the storage device electrode slurry was applied to the current collector, the appearance of the electrode was visually evaluated. In a randomly selected 5 cm × 5 cm field of view, the number of coating defects (foaming marks, streaks) with a diameter of 0.5 mm or more was counted and used as an indicator of foaming resistance, and evaluated according to the following criteria.
[0148] A: 0 to 1
[0149] B: 2 to 4
[0150] C: 5 or more
[0151] <Evaluation of Peel Strength (N / m)>
[0152] For the negative electrode for lithium secondary battery prepared in each embodiment and comparative example described later, the strength when the copper foil as the collector is peeled off the solid body (derived from the part of the negative electrode slurry prepared in the embodiment and comparative example) is measured. Specifically, the negative electrode slurry coating surface of the negative electrode for the obtained lithium ion secondary battery is bonded to the stainless steel plate using a double-sided tape (double-sided tape made by Nichiban), and a 50N force sensor (made by IMADA) is used to measure the 180° peel strength (peeling width is 10mm, peeling speed is 100mm / minute).
[0153] <Evaluation of initial charge and discharge efficiency (%) and DC resistance (Ω)>
[0154] For the lithium ion secondary batteries (coin batteries) produced in the following embodiments and comparative examples, a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo Systems Co., Ltd.) was used to implement the test. The resistance value when a current of 0.1 mA is circulated for 3 seconds after the initial charge is taken as the DC resistance. During charging, a constant current of 0.2C (1-1.2 mA) is charged to 0.01 V for the lithium potential, and then a constant voltage of 0.01 V is charged to the lithium potential until a current of 0.02 mA is reached. During discharge, a constant current of 0.2C (1-1.2 mA) is discharged to 1.5 V for the lithium potential. The lithium ion secondary battery is placed in a thermostatic bath at 25°C, and the initial charge and discharge is performed under the above conditions to measure the charge specific capacity (mAh / g), discharge specific capacity (mAh / g), and DC resistance (Ω). The initial charge and discharge efficiency (%) is calculated by the formula: (discharge specific capacity) / (charge specific capacity)×100.
[0155] <Evaluation of 1C charge capacity maintenance rate>
[0156] For the lithium ion secondary batteries (coin batteries) produced in the following embodiments and comparative examples, a commercially available charge and discharge tester (TOSCAT3100, manufactured by Toyo Systems Co., Ltd.) was used to perform a rate test after the initial charge and discharge. During charging, a constant current charge of 1.0C (5.0-6.0mA) was performed for the lithium potential until 0V. During discharge, a constant current discharge of 0.2C (1-1.2mA) was performed for the lithium potential until 1.5V. The lithium ion secondary battery was placed in a constant temperature bath at 25°C, and charge and discharge were performed using the above conditions. The battery cell charge capacity (mAh) at this time was measured. The 1C charge capacity retention rate (%) is calculated by (charge capacity (mAh / g) at 1.0C) / (charge capacity (mAh / g) at 0.2C) × 100.
[0157] ·Manufacturing of modified PVA
[0158] [Production Example 1]
[0159] (PVA-1)
[0160] 970 parts by mass of vinyl acetate and 30 parts by mass of methanol were added to a reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet, a comonomer addition port, and a polymerization initiator addition port, and the system was purged with nitrogen for 30 minutes while nitrogen was bubbled in. Monomethyl maleate was selected as a modified species (ethylenically unsaturated dicarboxylic acid monomer), and a methanol solution of monomethyl maleate (concentration 2%) was purged with nitrogen by nitrogen bubbling. The temperature of the reactor was started, and when the internal temperature reached 60°C, 0.1 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added to start polymerization. The methanol solution of monomethyl maleate was added dropwise to the reactor, and the monomer composition ratio in the polymerization solution was kept constant while polymerizing at 60°C for 2 hours, and then the polymerization was stopped by cooling. The total amount of ethylenically unsaturated dicarboxylic acid monomers added until the polymerization was stopped was 1.4 parts by mass, and the polymerization rate at the time of polymerization stop was 20%. Next, unreacted monomers were removed while adding methanol from time to time at 30°C under reduced pressure to obtain a methanol solution of a vinyl ester polymer (concentration of 30%). Next, 14.8 parts by mass of a 10% methanol solution of sodium hydroxide was added to 666.7 parts by mass of a methanol solution of a vinyl ester polymer prepared by further adding methanol to the methanol solution (the above-mentioned polymer in the solution was 200.0 parts by mass), and saponification was performed at 40°C. The above-mentioned polymer concentration in the saponified solution was 15%, and the molar ratio of sodium hydroxide to the vinyl acetate unit in the above-mentioned polymer was 0.016. After adding the methanol solution of sodium hydroxide, a gel-like substance was generated in about 20 minutes, so it was crushed with a pulverizer and then placed at 40°C for 1 hour for saponification. Thereafter, 500 parts by mass of methyl acetate was added to neutralize the residual alkali. After confirming that the neutralization was completed using a phenolphthalein indicator, a white solid was obtained by filtration. 2000 parts by mass of a mixed solution of methanol:methyl acetate = 20:80 was added to the white solid, and the mixture was left at room temperature for 3 hours and washed. After the washing operation was repeated 3 times, the white solid obtained by centrifugal dehydration was heated in a dryer at 95°C for 4 hours to obtain a modified PVA powder (PVA-1). The various manufacturing materials and physical properties of PVA-1 are summarized in Tables 1 and 2.
[0161] [Production Examples 2 to 9]
[0162] (PVA-2~PVA-9)
[0163] As shown in Table 1, the feed amounts of vinyl acetate and methanol, the type of the modified species (ethylenically unsaturated dicarboxylic acid monomer) used in the polymerization, the amount thereof added, the polymerization rate and other polymerization conditions, the saponification conditions such as the molar ratio of sodium hydroxide, and the drying conditions were changed. Various modified PVAs (PVA-2 to PVA-9) were produced in the same manner as the production method of PVA-1 (Production Example 1). The physical properties of each modified PVA are summarized in Table 2.
[0164] Compound (1)
[0165] As compound (1), the following acetylene glycol derivatives AG1 to AG4 were used.
[0166] AG1: 3,6-dimethyl-4-octyne-3,6-diol (in formula (1), R 1 is methyl, R 2 is ethyl, m=0, n=0)
[0167] AG2: 2,4,7,9-tetramethyl-5-decyne-4,7-diol (in formula (1), R 1 is methyl, R 2 isobutyl, m=0, n=0)
[0168] AG3: ethoxylate of AG2, (in formula (1), R 1 is methyl, R 2 isobutyl, the average value of m+n is 7)
[0169] AG4: ethoxylate of AG2 (in formula (1), R 1 is methyl, R 2 isobutyl, the average value of m+n is 20)
[0170] [Table 1]
[0171]
[0172] 1) MMM: monomethyl maleate
[0173] DMM: dimethyl maleate
[0174] MA: Maleic anhydride
[0175] [Table 2]
[0176]
[0177] [Example 1]
[0178] Hereinafter, an example of manufacturing an electric storage device using the PVA-1 manufactured as described above will be described.
[0179] Preparation of electrode slurry (negative electrode slurry) for power storage devices
[0180] PVA-1 and water were mixed and heated at 80°C for 1 hour to obtain a solution having a solid content concentration of about 10% by mass. The solution having a solid content concentration of 10% by mass and R in the formula (1) were mixed. 1 Methyl, R 2 A compound (AG3) having an isobutyl group and an average value of m+n of 7, artificial graphite (FSN-1, manufactured by Shanghai Shanshan Co., Ltd.) as a negative electrode active material, Super-P (manufactured by TIMCAL Co., Ltd.) as a conductive auxiliary agent (conductive imparting agent), and CMC (CMC DAICEL 2200, manufactured by DAICELMIRAIZU Co., Ltd.) as a thickener were placed in a dedicated container and kneaded using a planetary stirrer (ARE-310, manufactured by THINKY Co., Ltd.) to prepare a negative electrode slurry containing a binder for a storage device. When the ingredients were placed, the ratio of the components in the negative electrode slurry was such that the artificial graphite was 96 parts by mass, the Super-P was 1 part by mass, the total amount of the vinyl alcohol polymer and the compound (1) (i.e., PVA-1 and AG3) was 1.50 parts by mass, and the CMC was 1.5 parts by mass. That is, the composition ratio of the negative electrode active material, conductive aid, PVA-1, AG3 and thickener in the negative electrode slurry is, based on solid content, negative electrode active material: conductive aid: PVA-1: AG3: thickener = 96:1:1.35:0.15:1.5 (mass ratio).
[0181] ·Manufacturing of electrodes for power storage devices (negative electrodes for lithium-ion secondary batteries)
[0182] The negative electrode slurry obtained as described above was applied to a collector of copper foil (CST8G, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd.) using an applicator, and the appearance of the coating was evaluated. After drying once at 80°C for 30 minutes using a hot air dryer, a rolling process was performed using a roller press (manufactured by Hohsen Co., Ltd.). Afterwards, the battery electrode was punched out. After that, secondary drying was performed at 120° C. for 3 hours under reduced pressure to produce a negative electrode for a lithium ion secondary battery (negative electrode for a coin battery). The peel strength of the produced negative electrode for a lithium ion secondary battery was measured by the above method. The results are shown in Table 3.
[0183] ·Manufacturing of power storage devices (lithium-ion secondary batteries)
[0184] The negative electrode for lithium ion secondary battery obtained as described above was transferred to a glove box (manufactured by Miwa Seisakusho Co., Ltd.) under an argon atmosphere. A metal lithium foil (thickness 0.2 mm, ), a polypropylene system (Celgard#2400, manufactured by POLYPORE) is used as the separator, and the electrolyte is a mixed solvent system (1M-LiPF6, EC / EMC=3 / 7vol ratio, VC=2% by mass) obtained by adding lithium hexafluorophosphate (LiPF6) to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC), followed by adding vinylene carbonate (VC) (manufactured by Toyama Pharmaceutical Industries, Ltd.). In this configuration, a coin cell (2032 type) as a lithium ion secondary battery is prepared. For the prepared coin cell, the initial charge and discharge efficiency, DC resistance at 0.2C charge and discharge, and the battery cell charge capacity at 1.0C charge and discharge are measured using the aforementioned method. The results are shown in Table 3.
[0185] [Examples 2 to 9]
[0186] Except that PVA-2 to PVA-9 were used instead of PVA-1, the preparation of storage device electrode slurry (negative electrode slurry), the preparation of negative electrode for lithium ion secondary battery and the preparation of lithium ion secondary battery were carried out in the same manner as in Example 1, and the same measurements and evaluations were performed. The results are shown in Table 3.
[0187] [Example 10]
[0188] Using R in formula (1) 1 Methyl, R 2 The preparation of the storage device electrode slurry (negative electrode slurry), the preparation of the negative electrode for the lithium ion secondary battery and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and the same measurements and evaluations were performed. The results are shown in Table 3.
[0189] [Example 11]
[0190] Using R in formula (1) 1 Methyl, R 2 The preparation of the storage device electrode slurry (negative electrode slurry), the preparation of the negative electrode for the lithium ion secondary battery and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and the same measurements and evaluations were performed. The results are shown in Table 3.
[0191] [Example 12]
[0192] Using R in formula (1) 1 Methyl, R 2The preparation of the storage device electrode slurry (negative electrode slurry), the preparation of the negative electrode for the lithium ion secondary battery and the preparation of the lithium ion secondary battery were carried out in the same manner as in Example 1, and the same measurements and evaluations were performed. The results are shown in Table 3.
[0193] [Comparative Example 1]
[0194] Except that AG3 was not used, the preparation of storage device electrode slurry (negative electrode slurry), the production of negative electrode for lithium ion secondary battery and the production of lithium ion secondary battery were carried out in the same manner as in Example 1, and the same measurements and evaluations were performed. The results are shown in Table 3.
[0195] [Table 3]
[0196]
[0197] 2) Type of compound (1)
[0198] AG1: 3,6-Dimethyl-4-octyne-3,6-diol
[0199] AG2: 2,4,7,9-Tetramethyl-5-decyne-4,7-diol
[0200] AG3: Ethoxylate of AG2 (average value of m+n is 7)
[0201] AG4: Ethoxylate of AG2 (average value of m+n is 20)
[0202] As shown in Table 3, the electrical storage device electrodes of Examples were excellent in peel strength between the electrical storage device and the electrical storage device, and were also excellent in initial charge and discharge efficiency, 1C charge capacity retention rate, DC resistance, and anti-foaming.
Claims
1. A binder for an electrical storage device, comprising a vinyl alcohol polymer and a compound represented by the following formula (1). [Chemistry 1] In formula (1), R 1 and R 2 Each of them is independently an alkyl group having 1 to 4 carbon atoms, and m and n are each independently an integer of 0 to 25.
2. The binder for an electrical storage device according to claim 1, wherein The vinyl alcohol polymer contains a structural unit derived from an ethylenically unsaturated dicarboxylic acid monomer in an amount of 0.01 mol % to 10 mol % based on all structural units constituting the vinyl alcohol polymer, and the degree of saponification of the vinyl alcohol polymer is 60.0 mol % to 99.9 mol %.
3. The binder for an electrical storage device according to claim 2, wherein The ethylenically unsaturated dicarboxylic acid monomer includes at least one selected from the group consisting of maleic acid, monoalkyl maleate, dialkyl maleate, maleic anhydride, monoalkyl fumarate, and dialkyl fumarate.
4. The binder for an electrical storage device according to claim 1, wherein The R 1 is methyl, R 2 isobutyl, and m and n are less than 8 respectively. 5 . An electrical storage device binder solution comprising the electrical storage device binder according to claim 1 and a solvent. 6 . An electrical storage device electrode slurry comprising the electrical storage device binder solution according to claim 5 and an active material.
7. The electrical storage device electrode slurry according to claim 6, wherein The content of the electrical storage device binder is 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the active material. 8 . An electrical storage device electrode comprising a solidified body of the electrical storage device electrode slurry according to claim 6 or 7 and a current collector. 9 . An electric storage device comprising the electric storage device electrode according to claim 8 .
Citation Information
Patent Citations
Binder containing vinyl alcohol polymer, slurry, nonaqueous electrolyte secondary battery, and its electrode
JP1999250915A
Method for manufacturing positive electrode plate
JP2013037955A
Binder composition for secondary battery electrode, secondary battery electrode, and secondary battery
JP2017059527A
Positive electrode active material for nonaqueous electrolyte secondary battery, and method for producing the same, and nonaqueous electrolyte secondary battery
JP2017107827A